The Sermon Against Drunkenness Attributed to St Job of Pochaev as a Manifestation of Serbian and Ukrainian Literary Ties in the Sixteenth–Seventeenth centuries (The Fourteenth-Century Translation of George Hamartolus’s Chronicle) - Temčinas, Sergejus (Senoji Lietuvos literatūra, 2025)
The article is devoted to a short anonymous sermon against drunkenness in a now lost manuscript that once belonged to the Pochaev Monastery and is believed to have been written by St Job of Pochaev (c. 1551–1651) in his own hand. Nikolai Petrov, who studied the codex, named it ‘Pchela Pochaevskaya’ (Pochaev’s Melissa) and published this sermon as one of St Job’s works. The attribution of the manuscript and several anonymous sermons contained therein to Job of Pochaev was met with reasoned criticism but is nevertheless recognised by contemporary scholars. The article shows that this anonymous sermon against drunkenness is not an original work and could not have been written by St Job. It is an excerpt from the second ecclesiastical Slavic translation (Lětovnik) of George Hamartolus’s Byzantine chronicle, prepared by Bulgarian scribes and known only from its Serbian copies. It is presumed that this translation, unlike the much earlier one (Vrěmennik), did not reach the Eastern Slavs. However, the fact that the manuscript ‘Pchela Pochaevskaya’ contains an anonymous sermon against drunkenness, which is an excerpt from Lětovnik, shows that this translation was known in whole or in part in the Ruthenian (Ukrainian) lands of the Polish-Lithuanian Commonwealth where it could only have come from the Serbian manuscript tradition. Thus, this sermon is yet another example of the Serbian influence on early Ukrainian literature, unreported up until now, dating from the second half of the sixteenth century to the first half of the seventeenth century.
Keywords: church Slavonic homiletic; early Ukrainian literature; George Hamartolus’s chronicle; Job of Pochaev; Serbian and Ukrainian literary ties